2020
DOI: 10.1136/bmjgh-2020-002766
|View full text |Cite
|
Sign up to set email alerts
|

Allocating resources to support universal health coverage: policy processes and implementation in Malawi

Abstract: Optimising the use of limited health resources in low-income and middle-income countries towards the maximisation of health outcomes requires efficient distribution of resources across health services and geographical areas. While technical research exists on how efficiencies can be achieved in resource allocation, there is limited guidance on the policy processes required to convert these technical inputs into practicable solutions. In this article, we discuss Malawi’s experience in 2019 of revising its resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Across the four countries, QCN's emergence was supported by the network's alignment with national priorities to improve quality of care, as reflected in national health sector plans, as well as government efforts to make progress on the Sustainable Development Goals (SDGs). [77][78][79][80] A respondent from UNICEF described how these high-level government commitments were critical to QCN emergence in Bangladesh:…”
Section: Political Developmentsmentioning
confidence: 99%
“…Across the four countries, QCN's emergence was supported by the network's alignment with national priorities to improve quality of care, as reflected in national health sector plans, as well as government efforts to make progress on the Sustainable Development Goals (SDGs). [77][78][79][80] A respondent from UNICEF described how these high-level government commitments were critical to QCN emergence in Bangladesh:…”
Section: Political Developmentsmentioning
confidence: 99%
“…They used this approach to understand bottlenecks and facilitators to achieve UHC and to propose ways to improve the efficiency of health financing. One of the papers drew on a panel discussion with relevant stakeholders (e.g., Ministry of Health and Finance, WHO representatives) [ 42 ]; the other two studies aimed to revise a resource allocation formula and its implementation [ 43 ] and to predict the role played by BRICS [Brazil, Russia, India, China, South Africa] countries in the UHC movement [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, by Musango et al and Twea et al, reported how findings were shared and disseminated [ 42 , 43 ]. In these studies, the dissemination was part of the discussions that took part as part of the research process.…”
Section: Resultsmentioning
confidence: 99%
“…These include: (i) redistribution of existing fi nancial resources was not possible, (ii) the total resource envelope did not grow enough to achieve optimal distribution of the additional resources to operationalize the formula, and (iii) there was wavering political support to implement the formula due to regular changes at ministerial level at the MOHP. In 2019, a new formula was developed by updating data on population size, disease burden and coverage rates, unit costs of treatment, and cost variations across the districts (Twea et al 2020). The 2019 formula is also aligned to the country's health benefi t package, the EHP, which aims to advance the principles of health maximization, cost-effectiveness, and equity (Twea et al 2020).…”
mentioning
confidence: 99%
“…In 2019, a new formula was developed by updating data on population size, disease burden and coverage rates, unit costs of treatment, and cost variations across the districts (Twea et al 2020). The 2019 formula is also aligned to the country's health benefi t package, the EHP, which aims to advance the principles of health maximization, cost-effectiveness, and equity (Twea et al 2020).…”
mentioning
confidence: 99%